Research Of Transformation Processes In Linguistics (Eurasian Journal of Learning and Academic Teaching, 2026)
Linguotransformational processes are processes of change, new formation or adaptation of language units in different contexts. In this process, words, phrases and grammatical structures undergo semantic, phonetic, morphological, syntactic and pragmatic transformation. The concept of linguotransformational is one of the active terms in modern linguistics, formed from the combination of the words linguistics and transformation. The article discusses transformationology, linguotransformational processes and the poetics of linguistic changes that occur during the adaptation of dramatic works to the stage.